Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/bcr-2018-226697
|View full text |Cite
|
Sign up to set email alerts
|

Atypical testicular pain

Abstract: Testicular tuberculosis (TB) is rare, and, because of this, the lack of pathognomonic clinical features and its tendency to mimic other commoner conditions, the diagnosis is frequently delayed or may be missed. In this case, the initial clinical presentation was typical for bacterial epididymo-orchitis in a 38-year-old man. When the patient failed to improve with standard treatment including broadening of antibiotics, the diagnosis was re-considered because some unusual signs suggested testicular malignancy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
1
6
1
2
Order By: Relevance
“…However, suspicion of concomitant TB outside the urogenital tract should arise when these constitutional symptoms are present, such as pulmonary TB [ 13 ]. Compared with other reports in the literature, the average duration between onset of the symptoms and the definite diagnosis (mean 6.42 ± 7.0 months, range 0.3–36 months) in our study was longer, probably due to the insidious and asymptomatic onset of TBEO [ 5 , 14 16 ].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, suspicion of concomitant TB outside the urogenital tract should arise when these constitutional symptoms are present, such as pulmonary TB [ 13 ]. Compared with other reports in the literature, the average duration between onset of the symptoms and the definite diagnosis (mean 6.42 ± 7.0 months, range 0.3–36 months) in our study was longer, probably due to the insidious and asymptomatic onset of TBEO [ 5 , 14 16 ].…”
Section: Discussioncontrasting
confidence: 77%
“…In this situation, radical surgery is often unavoidable, which can be used for resection of the lesions and histopathological examination [ 4 , 6 , 13 , 20 ]. However, it is worth noting that Bedi et al has successfully treated a 38-year-old patient with TBEO by standard anti-tuberculous medications [ 14 ]. Besides, Abraham et al also reported an Ecuadorian man with TBEO who was cured with 6 months of drug therapy and no surgery was required [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms can mimic epididymo-orchitis as well as testicular cancer. Surgical intervention is avoidable if diagnosed in time, since GUTB responds well to standard TB treatment 9. This fits well with the regression of testicular symptoms from the remaining left testicle after initiation of treatment in our case.…”
Section: Discussionsupporting
confidence: 88%
“…Диагностика УГТ, как правило, запаздывает, что может вести к фатальным последствиям. Одни из основных причин -низкая настороженность в отношении туберкулеза, неумение распознать его среди других урологических заболеваний, под которые УГТ удачно маскируется [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionunclassified
“…Низкий уровень настороженности в отношении внелегочных локализаций туберкулеза и недостаточный уровень знаний приводят к поздней диагностике, когда терапевтические возможности исчерпаны и хирургическое вмешательство неизбежно [12]. Неэффективность антибактериальной терапии урогенитальных инфекций объясняют резистентностью патогена, в то время как это может иметь место туберкулез мочеполовой системы, протекающий под маской неспецифических заболеваний [17][18][19][20].…”
Section: Introductionunclassified